Practicing concrete universality : psychoanalysis as a political method : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Sociology, Massey University, Albany, New Zealand - McMillan, Christopher Ward (Massey University, 2006)
Lacanian psychoanalysis, embodied in contemporary thought by Slavoj Žižek's dialectical materialist rehabilitation of universality, enables a form of political analysis based on the possibility of structural change. Many political theorists argue that because psychoanalysis stresses the negative ontological base of the social (the Real) it is fundamentally conservative and nihilistic. Conversely, the very political value of psychoanalysis lies in its accent on the Real. However, there are two separate psychoanalytic perspectives on the Real. The idealist approach, which contends that every social construction is essentially conditional, is politically and theoretically limited. In contrast, Žižek's materialist perspective emphasises the fundamental fixity which lies in the necessary exclusion from a universal horizon. Thus, the main political insight of Lacanian psychoanalysis is not to reveal the contingency of the social, but rather the disavowed foundation on which these constructions are based; the concrete universal. This thesis argues for a Žižek-inspired psychoanalytic approach to the political which 'practices concrete universality'. Conversely, while Žižek himself considers his own theoretical endeavours as an application of this task, his work can appear to be at times abstract and obscure, such that the reader is not sure exactly what it is that Žižek is arguing. As such, this thesis seeks to develop a methodological position that practices concrete universality, taking on the fundamental insights of Žižek's position whilst grounding them in a methodology which can be applied for political intervention. The methodology analyses both the manner in which universal imaginaries domesticate the effect of the symptom (that which represents the concrete universal) and the possibilities for practicing concrete universality and in doing so evoking radical structural change. These possibilities are considered against global capital, which Žižek describes as a modality of the Real. Capital has produced a paradoxical and pressing condition in humanity is living both well beyond and beneath its material needs and the finite capacity of the planet to provide for those needs. Rather than seeking an impossible utopian revolution (the removal of all lack), by evoking the concrete universal it is hoped that humanity can rid itself of that lack which is historical contingent; global capital.
Keywords: Psychoanalysis -- Political aspects; Capitalism; Politics; Philosophy